Hubungan Perception Barriers Dengan Keaktifan Kunjungan Ibu Dalam Posyandu Balita - Widiya Wati, Roidah Hadis; Kurniawan, Ardhiles Wahyu; Hastuti, Apriyani (Jurnal Keperawatan Muhammadiyah, 2025)
The success of the posyandu program is very dependent on the active participation of the community, especially mothers with toddlers, but the reality on the ground is that the level of activity of mothers visiting posyandu is still often low. Various factors can influence this activity, one of which is the perceived barriers felt by the mother. Objective: The aim of this research is to analyze perception barriers with mothers' activeness in posyandu activities. Methods: This research design uses analytics with a cross-sectional approach. The population in this study were mothers who had participated in posyandu activities for at least 6 months. This research instrument uses a perception barriers questionnaire from the health belief model theory and documentation studies from the results of posyandu visits. Results: In this study the p-value obtained was 0.001. This shows that there is a relationship between perceived barriers and the activeness of mothers' visits to toddler posyandu. The main factors that influence perceptions of barriers include the mother's lack of understanding of the benefits of posyandu, lack of adequate posyandu facilities, and time constraints due to the mother's busy schedule. Conclusion: there is a significant relationship between perception barriers and the activeness of mothers' visits to toddler posyandu. The higher the perceived barriers, the lower the mother's active level of visitation.